PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN MARKET SHARE TERHADAP RETURN ON EQUITY (ROE) PADA PERUSAHAAN SEKTOR INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2022 - Herlina, Herlina; Susana Dewi (Universitas La Tansa Mashiro, 2023)
Return On Equity (ROE) has the ability to measure an entity's profit, of course the entity owner will pay more attention to ROE. The relationship between Current Ratio, Debt to Equity Ratio and Market Share on ROE is an interesting phenomenon to study. This research aims to determine the influence of the Current Ratio, Debt to Equity Ratio and Market Share both partially and simultaneously on ROE. The research method uses a quantitative/statistical study approach, testing data with the SPSS 26 for Windows program. The population of this research is all industrial companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sample was determined using a purposive sampling technique and 18 companies or 90 research data were obtained. The research results show that partially the Current Ratio has no effect on ROE, DER has an effect on ROE. Market Share influences ROE. Simultaneously, Current Ratio, Debt to Equity Ratio and Market Share influence ROE